Rethinking the Future Direction of Game Design Education: An Interdisciplinary Game Design Curriculum - LAU, Kung Wong (Journal of Games, Game Art, and Gamification, 2026)
This paper examines the growing need for an interdisciplinary approach to game design education in response to the increasing complexity and diversification of the global game industry. Contemporary game development demands not only technical proficiency but also creative, managerial, and analytical competencies that span multiple disciplinary domains. The study argues that integrating diverse fields, such as game design, game programming, artificial intelligence, art and aesthetics, data analytics, and management, can better equip students to understand the full lifecycle of game development and to respond effectively to industry challenges. The paper first reviews the historical development of curriculum design in creative and design education, highlighting the limitations of traditional mono-disciplinary models. It then discusses the significance of interdisciplinary curricula in fostering innovation, adaptability, and problem-solving skills. Focusing on the Hong Kong context, the study critically evaluates existing game-related programmes, identifying structural gaps between academic training and market expectations. To address these issues, a market survey was conducted to investigate the needs and perspectives of both industry stakeholders and students. Based on the findings, the paper proposes a re-envisioned interdisciplinary game design curriculum that emphasizes integrated learning and applied practice. The proposed curriculum aims to cultivate graduates capable of creatively applying advanced concepts in game design, game programming, and artificial intelligence, enabling them to address real-world challenges not only within the game industry but also across related sectors such as education, cultural industries, and digital entertainment.